Bioinformatics-based dynamics of cuproptosis -related indicators in experimental silicosis - Jiarui Xia; Chenchen Wu; Xiaofei Jin; Mingcui Ding; Chengpeng Zhang; Guangjie Hou; Changfu Hao; Wu Yao (Ecotoxicology and Environmental Safety, 2024)
Pneumoconiosis is one of the most serious occupational diseases worldwide. Silicosis due to prolonged inhalation of free silica dust during occupational activities is one of the main types. Cuproptosis is a newly discovered mode of programmed cell death characterized by the accumulation of free copper in the cell, which ultimately leads to cell death. Increased copper in the serum of silicosis patients, suggests that the development of silicosis is accompanied by changes in copper metabolism, but whether cuproptosis is involved in the progression of silicosis is actually to be determined. To test this hypothesis, we screened the genetic changes in patients with idiopathic fibrosis by bioinformatics methods and predicted and functionally annotated the cuproptosis-related genes among them. Subsequently, we established a mouse silicosis model and detected the concentration of copper ions and the activity of ceruloplasmin (CP) in serum, as well as changes of the concentration of copper and cuproptosis related genes in mouse lung tissues. We identified 9 cuproptosis-related genes among the differential genes in patients with IPF at different times and the tissue-specific expression levels of ferredoxin 1 (FDX1) and Lipoyl synthase (LIAS) proteins. Furthermore, serum CP activity and copper ion levels in silicosis mice were elevated on days 7th and 56th after silica exposure. The expression of CP in mouse lung tissue elevated at all stages after silica exposure. The mRNA level of FDX1 decreased on days 7th and 56th, and the protein level remained in accordance with the mRNA level on day 56th. LIAS and Dihydrolipoamide dehydrogenase (DLD) levels were downregulated at all times after silica exposure. In addition, Heatshockprotein70 (HSP70) expression was increased on day 56. In brief, our results demonstrate that there may be cellular cuproptosis during the development of experimental silicosis in mice and show synchronization with enhanced copper loading in mice.